An open-source 3D solar radiation model integrated with a 3D Geographic Information System. (February 2015) - Liang, Jianming; Gong, Jianhua; Zhou, Jieping; Ibrahim, Abdoul Nasser; Li, Ming
Abstract: Photovoltaic energy has become a popular renewable energy source for sustainable urban development. As a result, 3D solar radiation models are needed to facilitate the interactive assessment of photovoltaic potential in complex urban environments. SURFSUN3D is a visualization-oriented full 3D solar radiation model that has been shown to achieve efficient computation and visualization for 3D urban models. The present paper introduces a framework to integrate SURFSUN3D into a 3D GIS-based application to interactively assess the photovoltaic potential in urban areas.